2013
DOI: 10.1074/jbc.m113.496703
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Properties of Mammalian Elongin A and Its Role in Stress Response

Abstract: Background: Transcriptional elongation is a rate-limiting step in activation of stress response genes. Results: Optimal expression of stress response regulator ATF3 requires the elongation activity but not the ubiquitination activity of Elongin A. Conclusion: Elongin A plays a key role for the adequate expression of ATF3 in vivo. Significance: RNAPII ubiquitination and transcriptional elongation are independent activities of Elongin A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 68 publications
(80 reference statements)
4
29
0
Order By: Relevance
“…Methylation of EloA is needed for appropriate gene regulation by PRC2 in ES cells and for proper differentiation of ES cells. As EloA interacts with the CTD of RNA Polymerase II (Kawauchi et al, 2013), we propose that regulation occurs by a methylation induced alteration in the ability of EloA to impact transcription via the general transcription machinery. This results in increased downregulation of a subset of PRC2 targets, most of which are already expressed at low levels in WT cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methylation of EloA is needed for appropriate gene regulation by PRC2 in ES cells and for proper differentiation of ES cells. As EloA interacts with the CTD of RNA Polymerase II (Kawauchi et al, 2013), we propose that regulation occurs by a methylation induced alteration in the ability of EloA to impact transcription via the general transcription machinery. This results in increased downregulation of a subset of PRC2 targets, most of which are already expressed at low levels in WT cells.…”
Section: Discussionmentioning
confidence: 99%
“…This Elongin complex interacts with the phosphorylated form of Pol II C-terminal domain (CTD) and stimulates transcription elongation (Aso et al, 1996; Kawauchi et al, 2013). The complex is also part of a ubiquitin ligase complex along with Cullin5 and Rbx2 that drives degradation of stalled Pol II (Wilson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although our data raise the possibility that the Elongin A ubiquitin ligase might contribute to gene activation, it is important to emphasize that ligase-independent functions of Elongin are also likely to be important in this process, because transcription defects in Elongin A (Ϫ/Ϫ) or Elongin A knockdown cells can be rescued in whole or in part by Elongin A mutants that can stimulate Pol II elongation in vitro but do not support efficient Rpb1 ubiquitylation (10,11). Future studies investigating in more detail the biochemical mechanism(s) underlying regulation of assembly of the Elongin A ubiquitin ligase, the signals responsible for its induction, and the potential role of the ligase in Pol II transcription activation will be needed to resolve these issues.…”
Section: Discussionmentioning
confidence: 99%
“…Elongin C is similar in sequence to the SCF ubiquitin ligase subunit Skp1, whereas Elongin B is a ubiquitin-like protein (5,6). Elongin A has been implicated in activation of Pol II transcription in response to a variety of signals, including retinoic acid, ecdysone, notch, EGF, and TGF-␤, as well as stresses, such as heat shock, DNA damage, nutrient deprivation, and endoplasmic reticulum (ER) stress (7)(8)(9)(10)(11)(12). In at least some cases, Elongin A is thought to function in the release of promoterproximally paused Pol II (9).…”
mentioning
confidence: 99%
“…One example of a gene that is activated in a p38-dependent manner is ATF3, which known to be regulated at the level of transcriptional elongation in response to stress (43). It was reported that transcriptional elongation of ATF3 depends on Elongin A, a subunit of a multimeric complex that activates elongation by mammalian RNA Polymerase II (44).…”
Section: Discussionmentioning
confidence: 99%